2014
DOI: 10.1017/s0022377814000725
|View full text |Cite
|
Sign up to set email alerts
|

Role of Z-pinches in magnetic reconnection in space plasmas

Abstract: A widely accepted scenario of magnetic reconnection in collisionless space plasmas is the breakage of magnetic field lines in X-points. In laboratory, reconnection is commonly studied in pinches, current channels embedded into twisted magnetic fields. No model of magnetic reconnection in space plasmas considers both null-points and pinches as peers. We have performed a particle-in-cell simulation of magnetic reconnection in a three-dimensional configuration where null-points are present initially, and Z-pinche… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 40 publications
(40 reference statements)
1
12
0
Order By: Relevance
“…Pressure imbalance is a trigger for the initial explosive relaxation of the system. During this phase, half of the magnetic energy is converted to the particle energy (Olshevsky et al 2015b). The second stage of the evolution is characterized by randomly distributed, turbulent dissipation events taking place all over the domain.…”
Section: Results: "Multiple Nulls"mentioning
confidence: 99%
See 1 more Smart Citation
“…Pressure imbalance is a trigger for the initial explosive relaxation of the system. During this phase, half of the magnetic energy is converted to the particle energy (Olshevsky et al 2015b). The second stage of the evolution is characterized by randomly distributed, turbulent dissipation events taking place all over the domain.…”
Section: Results: "Multiple Nulls"mentioning
confidence: 99%
“…Further investigation has indicated that spiral magnetic nulls and current filaments exhibited strong energy dissipation and magnetic reconnection signatures. In contrast, energy dissipation events at the radial nulls were rather short-living and localized (Olshevsky et al 2015a(Olshevsky et al , 2015b. These findings motivated us to perform this survey of magnetic nulls in other kinetic simulations of space plasmas.…”
Section: Introductionmentioning
confidence: 97%
“…The simulation data in this study are from Olshevsky et al [, ], who initiate magnetic reconnection at Ω ci t = 0 and terminate it at Ω ci t = 52. The two snapshots we investigate are at the middle (Ω ci t = 26) and final (Ω ci t = 52) stages of the simulation.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In theory [ Greene , ; Lau and Finn , ] and simulations [ Galsgaard and Pontin , ; Olshevsky et al , , ], the properties and topology of magnetic nulls have been well studied. Generally, the null topology consists of a spine and a fan [ Priest and Titov , ; Parnell et al , ] and can have both “radial” and “spiral” features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation